KEDUDUKAN KOMISI PEMBERANTASAN KORUPSI SEBAGAI LEMBAGA NEGARA BANTU (STATE AUXILIARY INSTITUTIONS) - Indraputra, Tjokorda Gde; Bagiastra, I Nyoman (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 05, Oktober 2014, 2014)
This paper is about corruption eradication commission institutional position asstate aid (state auxiliary institutions). Problems that occurred about haziness norms ofthe position of the KPK, here the position of the Commission as State aid agencies areextra constitutional impressed. This paper aims to understand and know about theposition of institutional corruption eradication commission as state auxiliaryinstitutions. This paper is using the method of normative legal research with the type ofanalytical approach legislation (State Approach). This paper presented a study that theinstitute is to help state agencies in the implementation of the function does not positionitself as one of the three institutions of power according “trias politica”. Commission isthe state agency that aids in carrying out its duties and authorities are independent andfree from the influence of any power. While having the independence and freedom incarrying out its duties and authorities, but the Commission still dependent on otherbranches of power in matters relating to the organization. Here the Commission has arelationship with the legislature in the selection of the membership of the Commission,while it also has links with the judiciary regarding corruption court in which theCommission as an investigator and his accusers. Here the Commission is a state agencythat aids mandated by the Act.
Keywords: KPK State Auxiliary Institutions, State Institutions